Evaluación y plan de mejoramiento de la seguridad vial en la carretera Calpi-San Juan-Arenal ubicado en la provincia de Chimborazo. - Tenesaca Saca, Margoth Elizabeth (2017)
The purpose of this paper is to present the procedures to be developed in a road safety assessment, also illustrates the application of these procedures, a specific case, is done in the audit of roads in the operation, which is the type That greater application and development, as well as identifying the main causes of road insecurity on the Calpi- San Juan-Arenal road located in Ambato-Guaranda tie in the province of Chimborazo. After completion of the investigation and the results obtained through the analysis checklists of a safety audit (ASV), it was determined that there is an insecurity rate of 41%, and as an action to analyze Critical Factors and to provide maintenance To road safety, At the same time, it was identified that the most conflicting disorders in the pathway presented different causes such as: no vertical signaling, deteriorated horizontal signaling, bad BAT stripes, poor climatic conditions, velocity reducer by approximation to an intersection, etc. Are located on the abscissa 4 + 000 up to 6 + 000,6 + 000 up to 8 + 000 and 28 + 000 up to 30 + 000. The main guidelines for the development of the project have been the standards set forth: NEVI, 1. (2013). Book A Standards for Studies and Road Design. Quito: Volume N 2, IN IN. (2011). Ecuadorian Institute of Normalization (Road Signaling Part 2). Page 2 (2011). Ecuadorian Institute of Normalization (Road Signaling Part I). Quito, NEVI, 1. (2013). Book A "Procedures of Operation and Road Safety". Quito: Volume 5, and the Guide to Conduct a Road Safety Audit by Dourthe, A., & Salamanca, J. (2013). CON ASET